«The question concerning technology» in the cybernetic era: the case of Bostrom, Kurzweil and Kelly - Maureira-Velásquez, Marco (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
One of the fundamental questions that challenges philosophy is the leading role of technology in contemporary society. «The Question Concerning Technology» by Martin Heidegger is considered one of the essential reflections for philosophically analyzing the development of technology and its influence on everyday life. Following this track, we will problematize Heidegger’s proposal and present three current approaches that update this questioning in our current cybernetic era.